Temporal variations in plume flux: characterizing pulsations from tilted plume conduits in a rheologically complex mantle. Issue 1 (24th November 2022) - Neuharth, Derek; Mittelstaedt, Eric
SUMMARY: Along age-progressive hotspot volcano chains, the emplacement rate of igneous material varies through time. Time-series analysis of changing emplacement rates at a range of hotspots finds that these rates vary regularly at periods of a few to several tens of millions of years, indicative of changing melt production within underlying mantle plumes. Many hotspots exhibit at least one period between ∼2 and 10 Myr, consistent with several proposed mechanisms for changing near-surface plume flux, and thus melting rate, such as small-scale convection, solitary waves and instability formation in tilted plume conduits. Here, we focus on quantifying instability growth within plumes tilted by overlying plate motion. Previous studies using fluids with constant or temperature-dependent viscosity suggest that such instabilities should not form under mantle conditions. To test this assertion, we use a modified version of the finite element code ASPECT to simulate 400 Myr of evolution of a whole-depth mantle plume rising through the transition zone and spreading beneath a moving plate. In a 2-D spherical shell geometry, ASPECT solves the conservation equations for a compressible mantle with a thermodynamically consistent treatment of phase changes in the mantle transition zone and subject to either a temperature- and depth-dependent linear rheology or a temperature-, depth- and strain-rate dependent non-linear rheology. Additionally, we examine plume evolution in a mantle subject to a range of Clapeyron slopes for the 410 km (1–4 MPa K –1 ) phase transitions. Results suggest that plume conduits tilted by >67° become unstable and develop instabilities that lead to initial pulses in the transition zone followed by repeated plume pulsing in the uppermost mantle. In these cases, pulse size and frequency depend strongly on the viscosity ratio between the plume and ambient upper mantle. Based upon our results and comparison with other studies, we find that the range of statistically significant periods of plume pulsing in our models (∼2–7 Myr), the predicted increase in melt flux due to each pulse (3.8–26 × 10 −5 km 3 km −1 yr −1 ), and the time estimated for a plume to tilt beyond 67° in the upper mantle (10–50 Myr) are consistent with observations at numerous hotspot tracks across the globe. We suggest that pulsing due to destabilization of tilted plume conduits may be one of several mechanisms responsible for modulating the melting rate of mantle plumes as they spread beneath the moving lithosphere.